A Simulation and Optimization Framework for Evaluating Airline Schedule Robustness - Engström, Carl (My University, 2012)
The airline industry is constantly attempting to find new ways to combat delays and cancellations. Much of the work is done in two fields, the areas of robust airline scheduling and the area of airline recovery. Robust scheduling strives to make schedules that can be executed even though the airline is faced with minor disruptions such as delays. Recovery is focused more towards returning to the original schedule when faced with severe disruptions. A problem with these two areas is that they cannot fully be studied without first having to execute the schedule. This means that airlines must take risks when changing the way they schedule as they can only hope that the effects of their changes are good. For this purpose simulation of airline operations has been utilized in order to estimate these results beforehand. Several tools for simulation are available for use today, but the majority of them only simulate isolated areas or use greatly simplified models. Nevertheless, these have proven to be of great use, not only to airlines but also to other areas of aviation such as airport and airspace congestion control. This thesis shows how such existing simulation tools along with custom-written components can be combined with existing tools for recovery to create a simulation framework that can simulate the day-to-day operations of an airline in a realistic manner. This framework is then used to evaluate performance of airline schedules both from a cost-efficiency and robustness point of view. The obtained results are then compared to historical results and show how interesting performance measures can be obtained from the simulated data.
Keywords: Informations- och kommunikationsteknik; Människa-datorinteraktion (interaktionsdesign); Information & Communication Technology; Human Computer Interaction